Designed Optimization of Photoluminescence Emission for Carbon Dots With Bright Blue Emission at 416 NM and Mono-Exponential Decay Lifetime - Ruwaih, Mohammed Abbas; Soheyli, Ehsan; Naji, Jalil; Mutlugun, Evren; Kikhavani, Tavan; Sahraei, Reza; Abbas Ruwaih, Mohammed (Elsevier, 2025)
The presented study introduces optimized blue-emissive carbon dots (CDs) with high photoluminescence efficiency up to 65 % at 416 nm, large Stokes shift (69 nm), and full-width at half maximum (FWHM) of 73 nm. Xray photoelectron spectroscopy confirmed the formation of carbon-based bonds as the main component of CDs, with reliable amounts of O, S, and N as dopant components. These features, along with single-exponential time-decay profile at long average lifetime of 10.05 ns, supported the significant role of uniformly distributed mid-gap energy levels in the recombination process. The simplicity, low-cost, non-toxicity, and short reaction time of CDs, along with their excellent emission properties in the deep-blue region, make them suitable for use in environmental monitoring and high-contrast bioimaging.
Soheyli, Ehsan/0000-0002-1403-7934; Sahraei, Reza/0000-0001-7104-2126
Keywords: Carbon Dots; Deep-Blue Emission; High Quantum Efficiency; Uniform Energy Levels